Production, Characterization And Mechanical Evaluation Of Biocomposite Based On Banana Pseudostem Fibre And Agar - Nongman, Abdul Fattah (2018)
The study was conducted to develop a method of making biocomposite boards based on banana pseudostem fibre and agar. Banana pseudostem fibre and agar were both grounded to powder form. Fibre and agar mixtures of various ratios (100:0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, 10:90 and 0:100) were prepared by dry-blending. Biocomposite boards were produced by using the hot press method. The effect of the ratio of fibre to agar on the properties of the biocomposite boards was studied. The biocomposite boards were also characterised using Fourier Transform Infrared (FTIR) analysis,